Financial Satisfaction, Life Satisfaction and Psychological in Different Demographic Characteristics - Hidayat, Aisyah Indriaeni; Faturohman, Taufik (Granada El-Fath, 2024)
Examining the relationship between demographic factors and financial satisfaction, life satisfaction, and psychological factors is crucial in an increasingly complex financial landscape. An optimistic outlook on financial status leads to higher life satisfaction, suggesting that financial stability enhances overall satisfaction and happiness. The research investigates how sociodemographic traits influence subjective well-being, particularly focusing on financial satisfaction, psychological well-being, and life satisfaction. The method utilized in this study is descriptive statistical analysis. Data collection is conducted through surveys, with 210 total respondents. The findings highlight the complex relationship between sociodemographic characteristics and subjective well-being, indicating that shifting social norms significantly influence how people view their work situation and overall happiness.